Mycomystes nigriventris sp. nov. (Coleoptera: Erotylidae: Tritomini) from South America, with insights into the genus Mycomystes Gorham - de Castro Pecci-Maddalena, Italo Salvatore; Lopes-Andrade, Cristiano (Zootaxa, 2020)
Mycomystes nigriventris sp. nov. (Erotylidae: Tritomini) is described from South and Southeast Brazil. Mycomystes was described by Gorham to include a single species, Mycomystes ferrugineus Gorham, from Mexico. Since Gorham’s description, no other species was included in Mycomystes and its morphological limits to Mycotretus remain unclear. The new species described here is placed in Mycomystes due its oval body, conspicuously dilated tibiae, mentum plate subpentagonal, with a rounded outline, and terminal maxillary palpomeres more greatly widened than the terminal labial palpomeres. Mycomystes nigriventris sp. nov. differs from M. ferrugineus in the black ventral coloration, elytral punctation with rows of punctures uniform longitudinally and not confluent, outer side of protibia lacking conspicuous angle, and distributed in Southeast and South Brazil, with M. ferrugineus restricted to the northern and M. nigriventris sp. nov. to the southern Neotropics. Similarities in body shape, morphology of mouthparts, and male and female terminalia between M. nigriventris sp. nov. and four species of Mycotretus, which may belong in Mycomystes, are discussed. The detailed description provided here, including potential characters for a phylogenetic approach, will help in subsequent studies on Mycomystes and Mycotretus.